Legal Education against the Impact of Social Media in the Era of Information Disclosure for Pringgokusuman Residents in Yogyakarta - Ariyanti, Dwi Oktafia; Ramadhan, Muhammad (Indonesian Journal of Advocacy and Legal Services, 2019)
The purpose of this community service is to provide an understanding of the community on the impact of the use of social media in the current era of information disclosure. This is done so that people do not abuse the use of social media and are able to wisely utilize social media itself so as not to cause negative effects. Partners of community service activities are residents of Pringgokusuman, Gedongtengen, Yogyakarta. Education provided includes an understanding of the negative and positive impacts of using social media, the role of families, especially parents, in supervising the use of social media and the legal rules used to overcome problems arising from the use of social media. Many impacts arising from the use of social media. The negative impacts of using social media must be immediately prevented and acted upon because the negative impacts are spread very quickly and are detrimental to users and the community. In addition there are also positive impacts arising from the use of social media that can provide developments both in terms of social and material for the community.